Hak Hidup Sebagai Hak Asasi Manusia Dan Pelanggarannya Dalam Kasus Penyiksaan Andhika Lutfi Falah - Yuli Anggraini; Indi Sysilia Putri; Aisyah Nabila Putri (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the phenomenon of violent cases that result in death and raise profound questions about the effectiveness of legal protection of citizens' rights. This study uses a normative legal research method. The results of the study show that although the right to life is strongly guaranteed in law, its implementation and enforcement in the field still face complex ethical, sociological, and institutional challenges, especially when the victim's family chooses not to pursue legal action. To ensure more effective protection of the right to life, it is recommended that law enforcement officials strengthen proactive investigation mechanisms and increase transparency in the investigation process by publishing important results, such as forensic reports, to build public trust.